High-yielding seeds in unyielding environments: Examining the learning process of maize and bean producers in eastern and midwestern Uganda. (December 2021) - Riungu, Claris; Maat, Harro; Van Den Berg, Marrit
This paper examines the learning process by which farmers come to a decision to use newly introduced seeds which were promoted through demonstration plots in midwestern and eastern regions of Uganda. Framed as social and material interactions, we investigated the learning process of the demonstration plots using data from focus group discussions, interviews and a survey amongst 983 individuals. The results reveal several constraints that impede learning, resulting in an overall low awareness and adoption of the introduced seeds. Some of the most prominent constraints resulted from the selection of location and demonstration plot host, the distance of agro-dealers, at district headquarters, limited interactions amongst farmers and irregular involvement of farmers in the demonstrations. Moreover, the prominent role of agro-dealers at field days suggests that informing farmers about where to buy seeds was considered more important than explaining farmers how to grow these seeds profitably. This commercial focus of field days and demonstrations plots had negative consequences for the social learning. This paper contributes to the learning and adoption literature by showing that interactions amongst actors can improve or reduce the balance between didactic, social and environmental learning.